Effect of Bias Tasks through Cooperative Learning on EFL Learners’ Reading Comprehension Achievement: Gender in Focus - Alijani Tori, Afsaneh; Barjesteh, Hamed; Biria, Reza (Iranian Journal of Educational Sociology, 2022)
Purpose: An important facet in learning a language is expanding reading comprehension capability. The purpose of the present study was to investigate the impact of implementation bias tasks through cooperative learning and gender on the reading comprehension process of Iranian intermediate EFL learners. Methodology: Two groups of 30 learners took part as a control group and an experimental group. Primarily the participants took The Preliminary English Test (PET) as a reading comprehension pretest. Then the experimental group instructed through the precepts of bias tasks in cooperative learning. However, the control group instructed through traditional instruction. Finally, the participants took the reading comprehension post-test. Findings: The result of two-way ANCOVA revealed that bias tasks through cooperative learning improved EFL learners' reading comprehension skills. Conclusion: Also, findings demonstrated that the means reading scores did not differ noticeably between male and female groups on both pretest and posttest. This task in cooperative learning can be utilized either in the classroom or in instructors' training.